Acceptance and disparities of PET/CT use in patients with esophageal or gastro-esophageal junction cancer: Evaluation of mature registry data - Gupta, Vaibhav; Kulanthaivelu, Roshini; Metser, Ur; Ortega, Claudia; Darling, Gail; Coburn, Natalie; Veit-Haibach, Patrick (Frontiers in Nuclear Medicine, 2022)
Background/rationale PET/CT plays a crucial role in esophageal (EC) and gastroesophageal junction cancer (GEJ) diagnosis and management. Despite endorsement in clinical guidelines, variation in acceptance of PET/CT exists. The aim of this study was to assess the early use of PET/CT among EC and GEJ patients in a regionalized setting and identify factors contributing to disparity in access. Materials and methods Retrospective cohort study of adults with EC or GEJ between 2012 and 2014 from the Population Registry of Esophageal and Stomach Tumours of Ontario and Ontario Health (Cancer Care Ontario). Receipt of PET/CT and relevant demographics were collected, and statistical analysis performed. Continuous data were analysed with t-tests and Wilcoxon rank sum test. Categorical data were analysed with chi-square test. Kaplan–Meier methods were used to estimate median survival. Results Fifty-five percent of patients diagnosed with EC or GEJ between 2012 and 2014 received PET/CT (1321/2390). Eighty-four percent of patients underwent surgical resection (729/870), and 80% receiving radical treatment (496/622) underwent PET/CT. The use of PET/CT increased from 2012 to 2014. Male patients received more PET/CT than females (85% vs.78% p < 0.001). Median survival for the overall cohort was 11.1 months, 17.2 vs. 5.2 months among those who did and did not receive PET/CT and 35 vs. 27 months among the surgical cohort (p = 0.16). Conclusions We found that PET/CT use increased from 2012 to 2014 and that the majority of EC/GEJ patients being considered for curative therapy received PET/CT. There were also gender disparities identified. PET/CT appears to confer a potential survival benefit in our study, although our assessment is limited. Our findings may serve as learned lessons for other new imaging modalities, new indications for PET/CT or even for the introduction of new radiopharmaceuticals for PET/CT.